Penerapan Enterprise Resource Planning (ERP) Odoo untuk Manajemen Penjualan Sistem Home Delivery Restoran BCD - Selly Restika; Lufty Abdillah (UNIVERSITAS KALBIS, 2022)
BCD was a ordinary restaurant that serving dine in before it transforms to online-based restaurants. The rapid changes in business flow have caused the management to be unprepared to carry out an online sales system. Some of the problems that occur in the system such as errors in handling order management include manual data recording, the absence of menu inventory stock management and data flow that has not been integrated in each part of the work unit, resulting in a long order management process. The purpose of this research is to implement Odoo ERP using the ASAP method by configuring website and e-commerce modules, manufacturing modules, inventory modules, sales and invoicing modules to build a sales management system for a home delivery business system. The application produced in this study is an e-commerce website application for self-order customers and an internal system for managing incoming orders as well as procurement management and food menu supplies.